Molecular detection and antimicrobial resistance pattern of carbapenem-resistant Klebsiella pneumoniae isolated from patients with lower respiratory tract infections - Chowdhury, Shaheen Akhter; Paul, Swarna; Chowdhury, Fouzia Ahmed; Hossain, M. Moazzem; Barua, Banani; Nasrin, Masuma; Sultana, Afroza; Quddus, M. Abdul (International Journal of Research in Medical Sciences, 2026)
Background: Recently worldwide, carbapenem-resistant Klebsiella pneumoniae (CRKP) infection has attracted a lot of attention because of the scarcity of effective drugs and the severity of the illness as well as the high death rate. This study was conducted to assess the antimicrobial susceptibility profiles and the molecular identification of CRKP isolates that were obtained from patients with lower respiratory tract infection (LRTI) at a tertiary care hospital in Sylhet, Bangladesh. Methods: This cross-sectional study was conducted in the Department of Microbiology at Sylhet MAG Osmani Medical College, Sylhet, from July 2021 to June 2022. A total of 153 sputum samples were collected from adult patients (≥18 years) clinically diagnosed with LRTIs. Data were analyzed using SPSS version 26. Result: Among 153 sputum samples from LRTI patients, 66.0% showed bacterial growth, with Klebsiella pneumoniae accounting for 20.9% of isolates. The mean age was 52.43±17.12 years with male predominance (69.3%). Of the Klebsiella pneumoniae isolates, 25.0% were carbapenem-resistant (CRKP), among which 75.0% produced carbapenemase and 50.0% harbored the KPC gene. Overall isolates showed high resistance to cephalosporins (up to 81.2%) and moderate sensitivity to carbapenems (around 72–75%) and amikacin (56.2%). CRKP isolates demonstrated marked multidrug resistance, with high resistance to most antibiotics, including carbapenems (75.0%). Conclusion: In conclusion, one in every fourth KP isolate was CRKP, which highlighted the need for careful prescription of carbapenems for the therapy of infectious diseases with ESBL-producing KP. Among different genes conferring resistance to carbapenems, only the blaKPC gene was investigated in this study.